Choose your own learning adventure: Promoting academic integrity by designing choice in learning opportunities for online courses - Woodford, E.D. (Canadian Perspectives on Academic Integrity, 2021)
In higher education, is it necessary for every learner to take the same path through the course to complete the course? Detecting a number of plagiarism instances in a course resulted in the need to research and implement strategies to promote academic integrity. In a reflective study of teaching Indigenous Studies online over the past four years at two different institutions, this paper proposes how designing choices in online learning opportunities can promote academic integrity. Not without challenges, the constraints in implementation encountered over the fours years noted pre-designed online or continuous enrolment online courses where there is inability to personalize content or make revisions and difficulty building a relationship in order to personalize the course experience with larger online class sizes at some institutions and/or faculties.